SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DOSEN BERPRESTASI DENGAN MENGGUNAKAN METODE FUZZY DATABASE MODEL TAHANI (Fakultas Teknologi Informasi Universitas Stikubank (Unisbank) Semarang, 2014)
The best lecturer decision support system has been made in this research so it can be recommended to the chief efficiently by using the old system many total score of the lecturer work is the same, so it harm the chief to choose the best lecturer in Stikubank University. This proses using fuzzy database in tahani method in this proses by put the criteria data that made by the chief include the score, put the data limit/ score to decide the score into poor range, fair, good and excellent. This aplication we can know who is the best lecturer and see in detail the criteria include the complete score. If we found the same scoring so the system will compare the score of the scientific jurnal that has the highest scoreas the first rank. With this support system, hopefully that the chief will not have any difficulties to choose the best lecturer. Keywords : Fuzzy Database in Tahani Methode, Decision Support System, The best lecturer.